English - PETROVIĆ, Nađa; NESTOROVIĆ, Milica (Journal of process management and new technologies, 2026)
Digital transformation and digital platforms have led to significant changes in the way value is created, delivered, and captured in the economy and modern business. The aim of this paper is to analyze the structure of business models, monetization models, and the geographical scope of digital platforms awarded within the World Summit Awards (WSA) program in the period 2021–2025. The research is based on a mixed-method approach with a primary focus on qualitative analysis, applying content analysis and comparative analysis to a selected sample of 25 digital platforms. The results indicate the dominance of marketplace and fintech models, which account for more than two-thirds of the analyzed sample, while SaaS and AI platforms have a smaller but globally oriented presence. From a monetization perspective, transaction-based fees represent a significant revenue generation mechanism, while subscription models are primarily applied to standardized technological solutions. The findings reveal a clear correlation between the type of business model, monetization structure, and market expansion strategy. Interaction-based platforms tend to achieve regional growth, whereas standardized models demonstrate higher global adaptability. The contribution of this paper lies in the empirical analysis of platform development patterns across different environments, thereby enhancing the understanding of growth dynamics and internationalization of digital platforms, particularly in developing countries.